2017
DOI: 10.1002/ajpa.23348
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of microscopic alterations in modern and ancient undecalcified and decalcified dry bones

Abstract: The preservation of the bone microscopic structure appears to be influenced not only by age, but also by the burial context. Undecalcified bones appear to be more affected by taphonomical alterations, probably because of the thickness of the thin sections; on the contrary, decalcified thin sections proved to be able to tackle this issue allowing a better reading of the bone tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
1
10
1
2
Order By: Relevance
“…However, it is difficult to estimate the degree of alterations on a spatial scale larger than the microscopic field of view (here at 40x total magnification the field of view is c. 5 mm). Inter-observer variations cannot be avoided, while section thickness and decalcification can also affect GHI (or OHI) reliability for screening collagen preservation (Caruso et al, 2018). Inter-site variations (thermally older sites will have less collagen, e.g.…”
Section: Histological Preservationmentioning
confidence: 99%
“…However, it is difficult to estimate the degree of alterations on a spatial scale larger than the microscopic field of view (here at 40x total magnification the field of view is c. 5 mm). Inter-observer variations cannot be avoided, while section thickness and decalcification can also affect GHI (or OHI) reliability for screening collagen preservation (Caruso et al, 2018). Inter-site variations (thermally older sites will have less collagen, e.g.…”
Section: Histological Preservationmentioning
confidence: 99%
“…Generalized destruction (Fig. 3a) is accompanied by a loss of birefringence in the amorphous areas under cross polarized light, linked to a loss of collagen (Piepenbrink 1986;Garland 1989;Collins et al 2002;Caruso et al 2018). The two human petrous bones also have many amorphous, disintegrated areas of bone (Fig.…”
Section: Histological Preservationmentioning
confidence: 99%
“…Although the samples of the present study were collected from the same cemetery and remained in situ throughout the burial period in the same conditions, no correlation between bone matrix loss and period of inhumation was observed. Despite that, a recent study concluded that the more ancient samples are more extensive microscopic focal destruction and recent samples exhibited a better preservation of bone micromorphology [51]. Furthermore, five out of thirty-nine exhumed samples showed less no bone area than other cases, even after being buried for many years (Table 1).…”
Section: Fsi _2018mentioning
confidence: 96%